UK policymaker and expert perspectives on the smoke-free generation policy: a qualitative study - Rachael L Murray; Joanne Morling; Nathan Davies; Tessa Langley; Manpreet Bains (BMJ Public Health)
Introduction The UK smoke-free generation (SFG) proposal seeks to ban the sale of tobacco products to those born in or after 2009. There is substantial evidence for the benefits of raising the age of sale of tobacco but, despite several governments proposing SFG, the policy has faced significant challenge and has not been implemented at nation-state level. This study explores the context in which UK may be the first country to introduce SFG, identifies potential barriers and facilitators to SFG implementation and outlines possible approaches to SFG policy design.Methods We conducted 19 qualitative semistructured interviews with policymakers and health leaders in England, Scotland and Wales, including politicians, public health experts, academics, trading standards experts (responsible in UK for enforcing age restrictions on products), clinicians and civil society (charity sector) representatives. Data were analysed through Kingdon’s three policy streams (problem, policy and political) and organised using the framework approach.Results Participants conceptualised SFG as both addressing youth tobacco initiation and shifting societal norms. They agreed that all tobacco products should be included but had differing views on including e-cigarettes. Opinions on enforcement varied. Some believed minimal enforcement would suffice due to anticipated compliance, while others stressed the need for strong enforcement. All agreed enforcement should target retailers, not individuals. Politically, participants noted the rapid shift from advocates supporting Tobacco 21 to embracing SFG after government endorsement. Cohesive public health advocacy, maintaining cross-party support and public opinion and developing broader tobacco control policies were considerations for successful implementation.Conclusions Widespread support for SFG across expert, political and public opinion provides a strong foundation for its passing into law. UK public health actors swiftly took advantage of the opening of a tobacco control policy window. Those implementing SFG must carefully consider product coverage and its approach to enforcement.